T-cell redirecting therapies for B-cell non-Hodgkin lymphoma: recent progress and future directions - Russler-Germain, David A.; Ghobadi, Armin (Frontiers in Oncology, 2023)
Several key advances in the treatment of B-cell non-Hodgkin lymphoma (B-NHL) over the past two decades have strategically exploited B-cell lineage markers suitable for targeting by immunotherapies. First, the addition of the anti-CD20 monoclonal antibody (mAb) rituximab to a range of standard therapies conferred remarkable outcomes improvements in diverse settings, perhaps most prominently an overall survival advantage in newly diagnosed diffuse large B-cell lymphoma (DLBCL). Subsequently, multiple chimeric antigen receptor (CAR) T-cell therapies targeting CD19 have revolutionized the treatment of relapsed/refractory (rel/ref) DLBCL and are active in other B-NHL subtypes as well. Most recently, the longstanding aspiration to exploit patients’ endogenous T-cells to combat lymphoma has been achieved via T-cell redirecting therapies such as bispecific antibodies (BsAbs) that incorporate dual targeting of a T-cell antigen such as CD3 plus a B-cell antigen such as CD19 or CD20 expressed by the tumor. These novel agents have demonstrated impressive activity as monotherapies in patients with heavily pre-treated, rel/ref B-NHL of a variety of subtypes. Now, myriad clinical trials are exploring combinations of T-cell redirectors with targeted therapies, antibody-drug conjugates, conventional chemotherapy, and even new immunotherapies. Here, we highlight key landmarks in the development of T-cell redirecting therapies for the treatment of B-NHL, emerging evidence and lessons from recent clinical trials, and exciting new directions in this arena.